Imaging features of neurotoxoplasmosis: A multiparametric approach, with emphasis on susceptibility-weighted imaging. (2018) - Benson, John C.; Cervantes, Gustavo; Baron, Thomas R.; Tyan, Andrew E.; Flanagan, Siobhan; Lucato, Leandro T.; McKinney, Alexander M.; Ott, Frederick
Abstract: Background: Neurotoxoplasmosis is a common opportunistic infection in HIV/AIDS patients. Imaging identification of neurotoxoplasmosis assists in timely treatment. Purpose: To delineate the frequency of imaging abnormalities in patients with neurotoxoplasmosis on different MR sequences with a particular focus on SWI, and NCCT. Material and methods: The PACS database was retroactively searched over a 5-year period for patients with neurotoxoplasmosis who underwent MRI with SWI. Included patients had imaging features of neurotoxoplasmosis based on consensus review by two neuroradiologists, a clinical diagnosis of neurotoxoplasmosis at the time of MRI, and diagnostic confirmation based on positive serum or CSF serology or histopathology; 15 patients were included. The number of abnormal foci with restricted diffusion, increased FLAIR signal, intrinsic T1 hyperintensity, abnormal enhancement (CE-T1WI), and intrinsic hyperdensity on CT were recorded. Results: Intralesional susceptibility signal (ISS) foci on SWI were observed in 93.3% of patients with neurotoxoplasmosis (mean size 5.2 ± 3.8 mm). The average number of ISS foci was 3.9 per patient; 3/15 (20.0%) had a single ISS. Amongst other MR sequences, hyperintense FLAIR foci were the most common abnormalities observed (12.4 lesions/patient), followed by enhancing foci (8.2 lesions/patient), foci of restricted diffusion (7.1 lesions/patient), and intrinsic T1 hyperintense foci (3.4 lesions/patient). Abnormalities were least frequently observed on NCCT: abnormalities were identified in 5/15 (33.3%) patients, at a rate of 0.4 lesions/patient. Conclusion: ISS foci are present in the vast majority of neurotoxoplasmosis patients, likely representing hemorrhage. The incidence and frequency of other abnormal foci are highest on FLAIR, and lowest on NCCT.